2017
DOI: 10.1139/cjpp-2016-0681
|View full text |Cite
|
Sign up to set email alerts
|

Role of folate in nonalcoholic fatty liver disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a spectrum of chronic liver conditions that are characterized by steatosis, inflammation, fibrosis, and liver injury. The global prevalence of NAFLD is rapidly increasing in proportion to the rising incidence of obesity and type 2 diabetes. Because NAFLD is a multifaceted disorder with many underlying metabolic abnormalities, currently, there is no pharmacological agent that is therapeutically approved for the treatment of this disease. Folate is a water-soluble B vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 321 publications
(651 reference statements)
3
47
1
Order By: Relevance
“…Folic acid: The role of folic acid in alcoholic liver disease is already well known, while being less clear in NAFLD. We noticed a statistically relevant increase in the consumption of folic acid in our NASH patients; despite various studies showing a deficiency of this vitamin in NAFLD subjects [ 56 , 57 ], previous studies have not found out any correlation between folic acid serum levels and NAFLD evolution [ 55 , 56 , 57 ]. Moreover, a study conducted on 10 NASH patients receiving folic acid supplement for six months resulted in no improvements in liver damage markers [ 58 ].…”
Section: Discussioncontrasting
confidence: 73%
“…Folic acid: The role of folic acid in alcoholic liver disease is already well known, while being less clear in NAFLD. We noticed a statistically relevant increase in the consumption of folic acid in our NASH patients; despite various studies showing a deficiency of this vitamin in NAFLD subjects [ 56 , 57 ], previous studies have not found out any correlation between folic acid serum levels and NAFLD evolution [ 55 , 56 , 57 ]. Moreover, a study conducted on 10 NASH patients receiving folic acid supplement for six months resulted in no improvements in liver damage markers [ 58 ].…”
Section: Discussioncontrasting
confidence: 73%
“…Folate plays an essential role in lipid metabolism and folic acid supplementation can attenuate steatosis and improve oxidative stress in rodent models of NAFLD. Folate can also blunt the increase of inflammatory cytokines secreted by immune cells 32. Resveratrol has antioxidant, antiapoptotic and anti-inflammatory properties in patients with NAFLD 33.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no pharmacological agent approved for the treatment of NAFLD (Schuppan and Schattenberg, 2013;Sid et al, 2017). Folic acid is a water-soluble B vitamin that has been shown to modulate lipid metabolism and oxidative stress (Sarna et al, 2012).…”
Section: Introductionmentioning
confidence: 99%